2021
DOI: 10.3390/genes12101467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Codon Usage Patterns of Six Sequenced Brachypodium distachyon Lines Reveals a Declining CG Skew of the CDSs from the 5′-ends to the 3′-ends

Abstract: Brachypodium distachyon, a new monocotyledonous model plant, has received wide attention in biological research due to its small genome and numerous genetic resources. Codon usage bias is an important feature of genes and genomes, and it can be used in transgenic and evolutionary studies. In this study, the nucleotide compositions and patterns of codon usage bias were calculated using Codon W. Additionally, an ENC plot, Parity rule 2 and correspondence analyses were used to explore the major factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…We established the graphic with A3/(A3 + T3) as the y-axis and G3/(G3 + C3) as the x-axis [ 48 ]. The points around the central point (A = T, G = C) illustrate the degree and direction of base deviation [ 49 ]. The center point means that there is no deviation between natural selection and mutation pressure.…”
Section: Methodsmentioning
confidence: 99%
“…We established the graphic with A3/(A3 + T3) as the y-axis and G3/(G3 + C3) as the x-axis [ 48 ]. The points around the central point (A = T, G = C) illustrate the degree and direction of base deviation [ 49 ]. The center point means that there is no deviation between natural selection and mutation pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the average values of A3 + T3 and G3 + C3 were calculated as 0.5696 and 0.4304, respectively. These findings indicate an imbalance in codon usage between A + T and G + C at the third codon position, suggesting the influence of factors beyond mutation, natural selection pressure 41,42 , on codon usage patterns in GmWRKY transcription factors.…”
Section: Pr2-bias Plot Analysismentioning
confidence: 90%
“…PR2-plot analysis 24,25 positions the center point to indicate balanced base content, where A = T and G = C, suggesting an equilibrium between mutation pressure and natural selection 33 . Any deviation from this equilibrium implies a significant influence of natural selection on the gene compared to mutational pressure 25,[39][40][41] . In this study, the PR2 plot analysis revealed a tendency of occupancy toward the lower left or lower right region along the ordinate axis (A < T), with a comparable distribution on both sides of the abscissa axis (Figure 5).…”
Section: Pr2-bias Plot Analysismentioning
confidence: 99%
“…According to PR2, the center of the coordinate is A = T and G = C, indicating the absence of mutation pressure or natural selection on the codons. If there is mutation pressure or selection bias, the values deviate from the center (off-center) and the PCGs are unevenly distributed ( Wang et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%